Analysis of a pannexin 2-pannexin 1 chimeric protein supports divergent roles for pannexin C-termini in cellular localization. (August 2013) - Wicki-Stordeur, Leigh E.; Boyce, Andrew K. J.; Swayne, Leigh Anne
Abstract: Pannexins (Panxs) are a three-member family of large pore ion channels permeable to ions and small molecules. Recent elegant work has demonstrated that the Panx1 C-terminus plays an important role in channel trafficking. Panx2, another family member, has a longer and highly dissimilar C-terminus. Interestingly, Panx1 is readily found at the plasma membrane, while Panx2 is mainly present on intracellular membranes. Here we used overlap-extension cloning to create the first chimeric Panx, consisting of Panx2 with the Panx1 C-terminus (Panx2 Panx1CT ), to determine whether the Panx1 C-terminus influences the trafficking of Panx2. We are the first to observe a high level of co-localization between Panx2 and the endolysosomal enriched mannose-6-phosphate receptor. Interestingly this distinct localization of Panx2 is altered by the presence of the Panx1 C-terminus. These novel observations support previous data indicating the importance of the C-terminus in the control of Panx trafficking, and highlight the complexity of molecular signals involved.